Liberty or Death: The French Revolution - Tanner, Norman (Asian Horizons, 2016)
Peter McPhee, Liberty or Death: The French Revolution, New Haven and London: Yale University Press, 2016, pp. xvii + 488 (Hardback). ISBN 978-0-300-18993-3 This very remarkable book on the French Revolution of 1789 and its significance should appeal to general readers as well as scholars. The Australian author, currently professorial fellow at the University of Melbourne, has already published extensively on various aspects of the Revolution and allied topics. The present work is his crowning achievement: scholarly yet very readable, excellently produced and reasonably priced by Yale UP, well illustrated with maps, colour plates and a chronological outline, with extensive endnotes revealing his mastery of primary and secondary sources, a bibliography ‘of those printed sources most useful for this book,’ and a comprehensive index covering persons, places and topics.